Marketing globally : planning and practice - Samli, A. Coskun; Hill, John S. (Lincolnwood, Ill. : NTC Business Books, 1998)
This book contains four parts: The World Environment of International Marketing; Assessing the International Marketing Environment; Implementing International Marketing Strategies; and Coordinating and Controlling Marketing Programs.
Keywords: Marketing; Export marketing